Aggressive and anger behaviour affects ranking in taekwondo competition - Adam, Muhammad Asyraf Qabil (2018)
The objectives of this study is to investigate whether the level of aggression and anger are related to the taekwondo score. 379 Taekwondo athletes were recruited for this study. Participants completed a set of questionnaires of Competitive Anger and Aggressive Scale (CAAS) the data collected had been analysed. The results of this study revealed that, taekwondo performance was not affected by aggressiveness. In addition, anger was also not correlated with taekwondo performance. Plus, the results of this study also revealed that there was no association between aggressiveness and anger.